Graphene dispersed by pyrene‐terminated polyethylene glycol for reinforced epoxy composites. Issue 19 (11th January 2022) - Zheng, Yaochen; Xu, Hui; Jing, Heshun; Ren, Qingxin; Liu, Zhiqing; Gao, Zhengguo; Ban, Qingfu
Abstract: Incorporating graphene into epoxy composites is a facile strategy to improve their mechanical performances. However, the uniform and reliable dispersion of graphene within epoxy matrix remains a large challenge owing to the intrinsic difference in chemical properties. Here, pyrene‐functionalized polyethylene glycol (Py‐PEG‐Py) was easily synthesized and utilized as a dispersant to homogenize graphene. The effect of graphene loading on mechanical performances of reinforced epoxy composites was also investigated. As 0.01 to 0.05 wt% of graphene were incorporated in epoxy resin, the resulted composites exhibited excellent improvement in flexural strength and fracture toughness compared with neat epoxy. Typically, the flexural strength increased from 63.57 ± 1.5 MPa for neat epoxy to 108.36 ± 1.9 MPa (about 70.5%) for composite, and the fracture toughness ( K IC ) increased from 1.25 MPa m 1/2 for neat epoxy to 2.15 MPa m 1/2 (around 72%) for composite modified with only 0.04 wt% of graphene and 4 wt% of Py‐PEG‐Py. Crack pinning caused by well dispersed graphene was contributed to enhancement of the fracture toughness. This work reveals a tiny amount graphene can also largely improve the mechanical properties of composites, providing a feasible approach to disperse graphene and fabricate high performance graphene composites. Abstract :